PENGARUH PENERAPAN TEKNIK DUA TINGGAL DUA TAMU TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 12 SIJUNJUNG KECAMATAN LUBUK TAROK KABUPATEN SIJUNJUNG - Lastriani, Lastriani; Rismen, Sefna; Febriana, Rina (STKIP PGRI Sumbar, 2013)
The backgrounds of this research are that there are still many students acquiring low points and the mathematical concept apprehensions for the VIII-grade students of SMPN 12 Sijunjung of Lubuk Tarok District are low. The purpose of this research is to know whether the studentsâ mathematical concept apprehension by using two stays two guests technique is better than that using the conventional learning for the VIII-grade students of SMPN 12 Sijunjung of Lubuk Tarok District. This is an experimental research with Random to Subject design. The sampling technique is randomly. The instrument used in this research is final tests in the form of essay.Â Â Â Â Â Â Â The technique of data analysis is t test of one party with the assistance of software MINITAB. Based on the hypothesis testing, it is obtained that P value is similar to 0.000, meaning to be smaller than Î± = 0.05; so that the hypothesis is accepted. Then it can be concluded that the studentsâ mathematical concept apprehension by applying two stays two guests technique with handouts is better than that using the conventional learning for the VIII-grade students of SMPN 12 Sijunjung of Lubuk Tarok District of the year 2013/2014.